Translating Khmer Second Person Pronouns: Respect, Relations, and Social Conventions in the Gospel of John - Coffman, Kristofer Dale (The Bible translator, 2017)
This paper is a case study in the challenges of translating the Greek New Testament into Khmer, the language of Cambodia. The paper focuses on Khmer’s honorific system of second-person pronouns in order to show the difficulties of translating across language families and to highlight the amount of theological interpretation that every Khmer translation entails. Through three examples drawn from the Gospel of John, the paper explores the challenges that Jesus’ presence at the heart of Christian piety poses for a pronominal system that encodes social values such as relation and respect. The paper ends with a reflection on the possible advantages of the study of idiolect for the translation of honorific pronouns.